Recycling of multilayer films by reactive extrusion - Jeziórska, R. (Polimery, 2022)
Polyethylene, polyamide 6 and poly(ethylene terephthalate) multilayer films waste were recycled by reactive extrusion in order to produce thermoplastic polymers. These wastes were extruded together with PA 6 and PET functionalized with oxazoline groups (R-PA 6, R-PET), ethylene/ acrylic acid copolymer (EAA) or block copolymer styrene-ethylene/butylene- styrene-grafted-succinic acid (SEBS-g-SA). Used additives act as compatibilizers in the structurally heterogeneous initial wastes. Compatibilizers used, as well as wood fiber granulates (filler), improve the mechanical properties of compositions investigated.